Dzikr Therapy in Modern Society: A Study of Qodiriyah Naqsabandiyah Tarekat in Tirto Village - Ayuni, Diah; Abdini, Riski; Muawannah, Rizqoh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The problems faced by modern society are obvious with the development of increasingly advanced technology. Modernization helps humans develop their potential in living a routine life. Although it has a positive impact, technology often makes some individuals become lazy in worship. The splendor of modernization appears to make people complacent about their life goals. They do not seem to need religion because the shortcomings in the work are filled by technology. As for Sufism as a medium for spiritual improvement in carrying out obligations on every human being. Various problems of society that are closely related to the renewal of Science and even mentally hit the rapid flow of modernization. With bertasawuf, peace of mind against mental disorders experienced by modern society can be obtained. The importance of Sufism to fix the moral crisis in today's society is very necessary. Application of the teachings of Sufism in this study in the form of dhikr in Tariqa Qadiriyah Naqsabandiyah. The method used in this study with interviews, observations, and research studies related Tariqa Qadiriyah Naqsabandiyah conducted by the community in the village Tirto. The practice of Qadiriyah Naqsabandiyah Tariqa in the Tirto village community in the form of daily dhikr, weekly dhikr, monthly dhikr, and khataman dhikr which has the purpose of being a dhikr therapy for the cleanliness of the heart and soul because dhikr is considered to bring peace, increase faith and establish a relationship that has been connected.